Conceptualization of the Norwegian feed system of farmed Atlantic salmon - Skavang, Pernille Kristiane; Strand, Andrea Viken (Frontiers in Marine Science, 2024)
The total production of Norwegian Atlantic salmon is expected to increase considerably in the years to come. A majority of greenhouse gas emissions from aquaculture is accounted for by feed. To investigate and assess the sustainability and robustness of the feed system, a holistic perspective on the system is needed. We aim to conceptualize the current value chains of feed in Norway using the Food Systems Approach, existing literature, and stakeholder inputs. The Sustainable Development Goals include no specific mention of feed. Still, many Norwegian feed and animal producers link their sustainability work to these goals. This paper summarizes the sustainability perspectives of feed and animal producers in the aquaculture sector, as well as relevant background, regulations, and environmental and socio-economic drivers.